2021
DOI: 10.1039/d1tc00668a
|View full text |Cite
|
Sign up to set email alerts
|

Activating transition metal dichalcogenide monolayers as efficient electrocatalysts for the oxygen reduction reactionviasingle atom doping

Abstract: Recent studies in 2D transition-metal-dichalcogenides (TMDs) for electrocatalytic applications have mainly concentrated on MoS2, while the catalytic properties of the majority of TMDs with other metal compositions remain uncovered. This...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 69 publications
1
33
0
Order By: Relevance
“…The thermodynamic volcano diagram obtained based on the calculated adsorption energy of intermediates clearly indicates that Co or Ni‐doped 1 T ‐TiS 2 , 1 T ‐ZrS 2 , 1 T ‐NbS 2 , 1 T ‐TaS 2 , 2 H ‐TiS 2 and 2 H ‐TaS 2 acted as convenient ORR catalysts with overpotentials in the range of 0.32‐0.55 V, comparable to those of state‐of‐the‐art Pt/C catalysts. [ 334 ] The study further revealed that nonmetal doping, such as N or P doping, is also capable of effectively activating ORR activity with an overpotential range of 0.3–0.75 V, as shown in Figure 13c. Xiao et al.…”
Section: Transition Metal Non‐oxides: Structure and Electrocatalytic ...mentioning
confidence: 88%
See 2 more Smart Citations
“…The thermodynamic volcano diagram obtained based on the calculated adsorption energy of intermediates clearly indicates that Co or Ni‐doped 1 T ‐TiS 2 , 1 T ‐ZrS 2 , 1 T ‐NbS 2 , 1 T ‐TaS 2 , 2 H ‐TiS 2 and 2 H ‐TaS 2 acted as convenient ORR catalysts with overpotentials in the range of 0.32‐0.55 V, comparable to those of state‐of‐the‐art Pt/C catalysts. [ 334 ] The study further revealed that nonmetal doping, such as N or P doping, is also capable of effectively activating ORR activity with an overpotential range of 0.3–0.75 V, as shown in Figure 13c. Xiao et al.…”
Section: Transition Metal Non‐oxides: Structure and Electrocatalytic ...mentioning
confidence: 88%
“…[329,333] Recently, Tian and Tang, through systematic DFT calculations, stated that the surface S-layer on transition metal dichalcogenides is not effective for the ORR, which is limited by nonbonded ORR species, but when a defect is introduced by doping with a foreign material, the catalyst eventually turns into a good ORR catalyst. [334] They theoretically examined the catalytic performances of a series of pristine TMS 2 in different phase structures (1T-TMS 2 , 2H-TMS 2 ) and found that they exhibited quite poor activity toward the ORR due to a high adsorption energy barrier for ORR intermediates. However, the doping approach by first-row transition metals, such as Ni, Co and Fe, eventually served as positively charged centers and thereby enhanced O 2 adsorption and subsequently promoted hydrogenation reactions.…”
Section: Electrocatalytic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…18−21 Encouraged by graphene and carbon-based materials, more and more 2D materials have been increasingly explored as catalysts in ORR/ OER, such as BN, 22,23 MXenes, 24 phosphorene, 25−27 and 2D transition-metal-dichalcogenides (TMDs). 28,29 Recently, a new type of 2D material has garnered a great deal of attention. Ren and co-workers successfully synthesized 2D layered MoSi 2 N 4 with semiconductor properties (band gap ∼1.94 eV), high strength (∼66 GPa), and excellent stability by chemical vapor deposition (CVD).…”
Section: Introductionmentioning
confidence: 99%
“…The 2D graphene-based materials have gained much attention as active OER and ORR catalysts due to their high conductivity, low cost, and large surface area . Other carbon-based nanostructures with high electronic conductivity and uniformly distributed active sites are also widely studied as ORR catalysts. Particularly, the transition metal/nitrogen doped carbon materials (M–N–C), such as Fe–N–C and Co–N–C, have attracted tremendous research interests due to their low price and superior activity. Encouraged by graphene and carbon-based materials, more and more 2D materials have been increasingly explored as catalysts in ORR/OER, such as BN, , MXenes, phosphorene, and 2D transition-metal-dichalcogenides (TMDs). , …”
Section: Introductionmentioning
confidence: 99%